Pelo caminho do amar: Imaginando outros mundos na Educação Infantil a partir de Humberto Maturana e Ximena Dávila - Azzolin, Maria Aparecida Nunes (2019)
The PhD thesis herein is the result of the Post-Graduation Educational Program on Teaching, Knowledge and Professional Development of the Universidade Federal de Santa María (PPGE/UFSM). I base this thesis on the assumption that we are biological – cultural beings, meaning that nothing happens outside our biology although mediated by culture during the course of our lives. We experience, learn and imagine new worlds while living and sharing our life with others. This is an examination and an invitation to walk together, imagining a new world in the Path of Love for the Education of Children. My objective was to research the propositions of Humberto Maturana and Ximena Dávila in view of the future training of teachers based on the feeling of love as a transforming epistemologic principle. The methodology I used is original and unprecedented, was based on the prospects of the cultural biology and was organized into four stages: 1) to know / to obserb 2) to ponder 3) Motion / Action 4) Recursive pondering. The thesis herein is divided as a menu in a restaurant: First course; main course; dessert and coffee. The first course is meant to boost the appetite, open up the senses and sharpen the palate for the main course. The main course are the theoretical references that were used as a platform for the development of the Thesis / Degustation herein. The dessert in this banquet was developed as a sweet trait that must be chewed slowly, because it comprises the methodology. And the coffee time is the moment for the final reflections. I made this analogy because I believe that in cooking, as in the process of educating, it is necessary the training, care and love. The idea behind all this is that the reader can taste slowly every word, every idea, thinking of new possibilities. In my degustations / readings I concluded that all we have in our life is the present moment, that changes constantly while we are living it. To be alive is something that happens as a matter of constant flowing so it can and must be tasted with utmost pleasure. To be alive just happens, effortlessly. To live is beautiful, light and colourful, and that is the way the school should be because that is the place where the awakening takes place. The awakening of life, of happiness. The school is the place to make mistakes, to experience new flavours, smells and textures. The school should be a place of marvels. To be marvelled by knowledge. It is not a place for competitions or punishments. It is the place where teacher and student should dance, grow and learn together. A place where each one can be what it really is and where the mistakes are only another way of learning. The child that does not possess the ability of the caring touch, look and listening of others will hardly own those same features as an adult. We learn to love while being loved. We learn to listen to others while being listened to. We learn to respect others while being respected. The adult that cannot love, touch, listen or feel others has not been taught those experiences while being a child. They were not being raised with love and to feel, to touch and to express themselves sincerely and spontaneously.